Listeria-based immunotherapy directed against CD105 exerts anti-angiogenic and anti-tumor efficacy in renal cell carcinoma - Oladejo, Mariam; Nguyen, Hong-My; Silwal, Ashok; Reese, Britney; Paulishak, Wyatt; Markiewski, Maciej M.; Wood, Laurence M. (Frontiers in Immunology, 2022)
Targeting tumor-associated angiogenesis is currently at the forefront of renal cell carcinoma (RCC) therapy, with sunitinib and bevacizumab leading to increased survival in patients with metastatic RCC (mRCC). However, resistance often occurs shortly after initiation of therapy, suggesting that targeting the tumor-associated vascular endothelium may not be sufficient to eradicate RCC. This study reports the therapeutic efficacy of a Listeria (Lm)-based vaccine encoding an antigenic fragment of CD105(Lm-LLO-CD105A), that targets both RCC tumor cells and the tumor-associated vasculature. Lm-LLO-CD105A treatment reduced primary tumor growth in both subcutaneous and orthotopic models of murine RCC. The vaccine conferred anti-tumor immunity and remodeled the tumor microenvironment (TME), resulting in increased infiltration of polyfunctional CD8+ and CD4+ T cells and reduced infiltration of immunosuppressive cell types within the TME. We further provide evidence that the therapeutic efficacy of Lm-LLO-CD105A is mediated by CD8+ T cells and is dependent on the robust antigenic expression of CD105 by RCC tumor cells. The result from this study demonstrates the safety and promising therapeutic efficacy of targeting RCC-associated CD105 expression with an Lm-based immunotherapy.